Bibliographic Citations in Biochemistry : A Chronological Analysis - Gopinath, M. A. (Journal of Information and Knowledge, 1985)
Presents an analysis of references given at the end of the technical papers in Journal of Physiology, Experiemental Cell Research, Journal of Comparative Neurology and Journal of Molecular Biology. Sample articles were chosen for subject coterminous with each other for three decades 1950, 1960, and 1970. The analysis resulted in ranking of journals, increase or decrease of reference articles, variety of documents cited and age of references. It was found that journals have greater self-citations and journals were the most frequently cited source of information. It was also found that older documents have fairly good impact values in the field of Biochemistry. The data elements in the bibliographic citations remain same over the period 1950's to 1970's. The secondary information services have been identified as important sources for finding references and verifying them.